2020
DOI: 10.3390/en14010100
|View full text |Cite
|
Sign up to set email alerts
|

Energetic-Environmental-Economic Feasibility and Impact Assessment of Grid-Connected Photovoltaic System in Wastewater Treatment Plant: Case Study

Abstract: Wastewater treatment plants and power generation constitute inseparable parts of present society. So the growth of wastewater treatment plants is accompanied by an increase in the energy consumption, and a sustainable development implies the use of renewable energy sources on a large scale in the power generation. A case study of the synergy between wastewater treatment plants and photovoltaic systems, aiming to improve the energetic, environmental and economic impacts, is presented. Based on data acquisition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…The parameters mentioned in Table 21 are fetched by the commercial PV software from its library of components from different manufacturers. These values can vary depending upon the location and manufacturer, similar to the studies [82][83][84].…”
Section: Technicalmentioning
confidence: 80%
See 1 more Smart Citation
“…The parameters mentioned in Table 21 are fetched by the commercial PV software from its library of components from different manufacturers. These values can vary depending upon the location and manufacturer, similar to the studies [82][83][84].…”
Section: Technicalmentioning
confidence: 80%
“…Table 23 summarizes the assumptions considered during the financial analysis. Some of these assumptions are specific to geographical location and can vary by some margin, similar to the reference [82]. The UK's base inflation rate was 2.1 at the point of this analysis and was adjusted conservatively.…”
Section: Financialmentioning
confidence: 99%
“…The results of the studies carried out in different places are generally reflected as operational outputs. Moreover, the ReCiPe method helps in accessing results in the three primary categories for determining endpoint, namely: quality of the ecosystem, resources, and human health [10]. The various factors considered under the quality of the ecosystem are noted below:  "Agricultural land"  Occupation  Climate Change  "Marine Eco-toxicity"  "Freshwater Eutrophication Potential" (FEP)  "Terrestrial Eco-toxicity Potential" (TETP)  "Freshwater Eco-Toxicity Potential" (FETP)  "Global Warming Potential" (GWP) Similarly, human health can also be sub-divided into various sub-categories for better understanding of the impact of "wastewater treatment plants".…”
Section: Resultsmentioning
confidence: 99%
“…More recent papers have carried out a quantitative analysis of the solar energy generated from WWTPs where specific 105 Californian WWTPs were examined, of which 41 installed a solar PV system [18]. In [19], it was shown that the synergy of small and medium WWTPs with PV is of great interest from an energetic/environmental/economic point of view; it was stated that "this synergy is worth exploring and implementing on a large scale for all new WWTP". Therefore, more studies are necessary.…”
Section: Introductionmentioning
confidence: 99%